Seasonal incidence of foliar diseases of Cowpea (Vigna unguiculata L.Walp) and their eco-friendly management through shifting of planting time - Roy, Sanchari; Basu, Amitava (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2021)
A thorough study was conducted on foliar diseases of cowpea under widely cultivated cowpea producing areas of Nadia & Hooghly district of West Bengal. The areas were Mondouri, Jaguli Instructional farm, Muragacha, Rajberia, Chakdaha, Madanpur, Basantapur, Kalyani Incheck farm, Kalyani “C” block farm under Nadia district and Mogra under Hooghly district. The fixed plot survey was conducted during Pre-kharif, Kharif & Rabi season. Seven fungus has been isolated during survey period and these are- Alternaria alternata, Colletotrichum capsici, Corynespora cassicola, Fusarium ciceri, Rhizoctonia solani, Sclerotium rolfsii, Curvularialunata. Among these pathogens, Alternaria alternata, Colletotrichum capsici,Corynesporacassicola found to be most dominating pathogen during Pre-Kharif, Kharif & Rabi season respectively.Shifting of planting time was carried out for avoiding the plant pathogen at a particular growth stage of the crop. Five cultivars (Kashikanchan, Triguna, Manikanchan, KSP-170 &Arkagarima) were selected for the experimental trial for three different seasons against the main dominating pathogens. For Pre-Kharif planting of cowpea, the 1st week of March, for Kharif planting time, 1st week of June were established as most profitable. During Rabi season for planting of three varieties viz.Kashikanchan, Manikanchan& KSP-170, 4th week of November and for Triguna&Arka Garima, 2nd week of November were found most profitable due to least incidence of diseases and maximum yield.